CLIMATIC AND ENVIRONMENTAL CONTROLS ON THE VARIATION OF C3 AND C4 PLANT ABUNDANCES IN CENTRAL FLORIDA FOR THE PAST 62,000 YEARS - Huang Y.; Shuman B.; Wang Y.; Webb III T.; Grimm E.C.; Jacobson G.L. (My University, 2006)
Lake Tulane provides one of the few continental sediment records beyond the late glacial period (~ 15,000 cal years B.P.) for eastern North America. Its continuous, organic-rich sediment has yielded pollen assemblages that date back 62,000 years. Here we report the first organic geochemical characterization of the sediment core from Lake Tulane based on compound-specific carbon isotopic analyses of higher plant leaf waxes. Our millennium-resolution carbon isotope data allow us to quantitatively assess the variations in the relative abundances of C3 and C4 plants in Central Florida under contrasting climate conditions and different atmospheric pCO2 levels during the last glacial-interglacial cycle. Specifically, our results indicate large changes in the relative abundance of C3 and C4 plants, with ~ 40% higher input from C4 plants during the last glacial maximum (LGM) than during the Holocene. During the last glacial period, C4 plant abundance decreased dramatically during the pine phases when precipitation increased, indicating that increasing precipitation overrode the impact of low atmospheric pCO2, leading to expansions of C3 plants. Our results provide new insights on the forcing mechanisms and first quantitative estimates on the C3 and C4 plant variation in central Florida for the last 62,000 cal years. © 2005 Elsevier B.V. All rights reserved.
Keywords: C3 AND C4 PLANTS; COMPOUND-SPECIFIC CARBON ISOTOPE ANALYSIS; LAKE TULANE; LEAF WAXES; SEDIMENT RECORD; Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен